In The Framework of External Cooperation, Modernized Laboratories and High-Yielding Wheat Varieties Should be Introduced - Erkinovich, Tuyev Fazliddin (International Journal on Integrated Education, 2026)
In recent years, innovative approaches, scientific and technical achievements and international cooperation have been gaining special importance in the development of agriculture. In particular, the modernization of modern agricultural laboratories and the introduction of high-yielding wheat varieties within the framework of projects implemented with foreign partners in Samarkand, Bukhara and Navoi regions serve to increase productivity and ensure food security. This once again confirms the effectiveness of implementing scientific approaches in agriculture.